Revisiting National Journalism Cultures in Post-Communist Countries: The Influence of Academic Scholarship - Harro-Loit, Halliki (2015)
The aim of this exploratory study is to develop the concept of the actor approach and journalism culture by adding a factor that has been more or less overlooked: academic scholarship. The paper also proposes to use the concept “discursive institutionalism” in order to clarify what knowledge and opinions about media are formed in the interaction of media institutions and academia with other institutions in society (e.g. educational, political and judicial). The concept “discursive institutionalism” includes the role of academia in providing new knowledge by conducting and disseminating research on the national and international levels, and this deserves greater attention. Although it is a common understanding that the role of academia is to prepare young professionals, it is less discussed how national media research and journalism education, in synergy, can create and maintain a collective understanding regarding the role and performance of national journalism in turbulent times. The paper is a meta-analysis of published research, and the empirical part of the study includes a close reading of academic articles, reports and conference presentations that are available in English about media in Central and Eastern European (CEE) countries. Examples of research from selected CEE countries provide a descriptive view of problems and tendencies concerning media performance in these countries. The proposed analytical approach aims to connect these problems and provide ideas for further research.